Patterns and drivers of regeneration of tree species in forests of peninsular Spain - Vayreda, Jordi; Gracia, Marc; Martínez-Vilalta, Jordi; Retana, Javier (Journal of Biogeography, 2013)
Aim Our study aimed to identify and explore the main factors that influence tree recruitment of multiple species at a regional scale across peninsular Spain, an understanding of which is essential for predicting future forest species composition in the face of ongoing environmental change. The study focused on the dynamics of the key transition phase from saplings to adult trees. Location The forests of peninsular Spain. Methods We used the extensive network of plots sampled in two consecutive Spanish national forest inventories (> 30,000 plots) to identify the factors that determine regeneration patterns of the 10 most abundant forest species of Spain at relatively large temporal (c. 10 years) and spatial scales (across Spain): five coniferous species of Pinus (pines) and five broadleaved species of the genera Fagus and Quercus. We fitted separate generalized linear models for the pine species and the broadleaved species to assess the response of sapling abundance and ingrowth rate to the spatial variability of climate (temperature, water availability and recent warming), forest structure (tree density, understorey and overstorey canopy cover, and basal area change) and disturbances (previous forest logging, wildfires and grazing). Results Mean sapling abundance was four times higher for broadleaved species than for pines, while mean annual ingrowth was twice as high. Sapling abundance and ingrowth rate were mainly determined by stand structure, both in pines and broadleaved trees. The direct effects of disturbances and climate were comparatively smaller, and there was no detectable effect of recent warming. Main conclusions The higher values of ingrowth rate of broadleaved species can be explained by their ability to maintain a higher sapling bank due to their greater shade tolerance. This differential response of pines and broadleaved species to canopy closure suggests a probable increase in broadleaved species at the expense of pines. This transition could occur earlier in stands with faster canopy closure dynamics. Spatially explicit, mixed-species demographic models incorporating both the ingrowth and the tree mortality components are needed for predicting the composition of future forests.
Keywords: Broadleaved trees; climate warming; conifers; disturbance; ingrowth rate; national forest inventory; sapling abundance; shade tolerance; Stand Structure; Water availability

Spatial Patterns and Predictors of Forest Carbon Stocks in Western Mediterranean - Vayreda, Jordi; Gracia, Marc; Canadell, Josep G; Retana, Javier (Ecosystems, 2012)
Mediterranean semi-arid forest ecosystems are especially sensitive to external forcing. An understanding of the relationship between forest carbon (C) stock, and environmental conditions and forest structure enable prediction of the impacts of climate change on C stocks and help to deﬁne management strategies that maximize the value of forests for C mitigation. Based on the national forest inventory of Spain (1997–2008 with 70,912 plots), we estimated the forest C stock and spatial variability in Peninsular Spain and, we determined the extent to which the observed patterns of stand C stock can be explained by structural and species richness, climate and disturbances. Spain has an average stand C stock of 45.1 Mg C/ha. Total C stock in living biomass is 621 Tg C (7.8% of the C stock of European forests). The statistical models show that structural richness, which is driven by past land use and life forest history including age, development stage, management activities, and disturbance regime, is the main predictor of stand tree C stock with larger C stocks in structurally richer stands. Richness of broadleaf species has a positive effect on both conifer and broadleaf forests, whereas richness of conifer species shows no signiﬁcant or even a negative effect on C stock. Climate variables have mainly an indirect effect through structural richness but a smaller direct predictive ability when all predictors are considered. To achieve a greater standing C stock, our results suggest promoting high structural richness by managing for uneven-aged stands and favoring broadleaf over conifer species.
Keywords: conifer and broadleaf forests; fire disturbance; Forest management; national forest inventory; Peninsular Spain; structural richness; tree carbon stock; Tree species richness; understory carbon stock; Water availability

CARACTERIZACION ESTRUCTURAL DE LOS ENCINARES DE CATALUÑA Marc - Gracia, Marc; Retana, Javier; Espelta, Josep Maria; Gené, Caries (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
In this paper, a characterization of structure of holm-oak forests in the Northeastem Iberian Peninsula is proposed. The study is based on different features of these forests, both at the stand and at the individuallevel.
Keywords: Basal area; density of stems; Forest structure; holm-oak; Quercus ilex; size distri bu ti on